THE DETERMINANTS OF HOUSEHOLD FINANCIAL MANAGEMENT OF THE SHARE-TAXI DRIVER’S WIFE IN BANDUNG - Verdana, Faza; Nainggolan, Yunieta Anny (Journal of Business and Management, 2021)
Abstract: Covid-19 pandemic has led the share-taxi industry into a precarious state. According to the previous studies, household financial management is one of the important factors to determine the economic welfare of a household finance condition. The objective of this research is to identify the determinants of household financial management of the share-taxi driver’s wife. The data of this research gathered from the questionnaire referred to (DEFINIT, SEADI and OJK, 2013) for basic financial literacy as well as Bank Indonesia (2013) for household financial management. The questionnaires are filled by 103 respondents and analyzed with multilinear regression. The result of this research showed that the basic financial literacy level of share-taxi driver's wife is still low and the household financial management of share-taxi driver's wife is categorized as medium. Moreover, monthly income and basic financial literacy has a positive and significant effect towards household financial management.Keywords: Covid-19 Pandemic, Household Financial Management, Basic Financial Literacy, Demographics Profile, Share-Taxi Driver’s Wife, Multilinear Regression